Evaluating the Impact of Immunotherapy on Long-term Survival Rates in Lung Cancer Patients in Sub-urban Areas in Bangladesh - Md Khorshed Alam; S M Nazmul Hasan; Sharif Ahmed; Soumittra Kumar (Research Synergy Foundation, 2024)
Lung cancer is a leading cause of cancer mortality worldwide, with an exceptionallyhigh incidence and poor outcomes in the suburban areas of Bangladesh due to limited healthcare infrastructure. Immunotherapy is a promising treatment modality for non-small-cell lung cancer (NSCLC), but its impact on resource-limited settings underexplored. This study evaluated the effect of immunotherapy on long-term survival rates among patients with lung cancer in the sub-urban districts of Cumilla and Feni, Bangladesh. A mixed-methods approach was used, involving 22 patients with NSCLC who were divided equally into the immunotherapy group and control group receiving conventional chemotherapy. Quantitative data on survival outcomes were analyzed using Kaplan–Meier estimates and Cox proportional hazard models to adjust for confounders. Qualitative data were collected through semi-structured interviews with patients in the immunotherapy group, focusing on access barriers, perceptions, side effects, and support systems. The immunotherapy group had a median overall survival of 18 months compared with 12 months in the control group (p = 0.03), with an adjusted hazard ratio of 0.55 (95% CI: 0.32–0.95, p = 0.033), indicating a 45% reduction in the risk of death. Qualitative findings revealed significant financial and geographical barriers to receiving immunotherapy. Patients reported a mix of hope and anxiety regarding treatment efficacy and side effects, with support systems playing a crucial role in treatment adherence and coping mechanisms. Immunotherapy significantly improves long-term survival rates among patients with lung cancer in sub-urban Bangladesh. Addressing financial constraints, enhancing healthcare infrastructure, and strengthening support systems are essential to maximize the therapeutic potential of immunotherapy in resource-limited settings.